Dissociation of synthetic Holliday junctions by E. coli RecG protein. - Lloyd, R G (EMBO J, 1993)
The RecG protein of Escherichia coli is needed for normal levels of recombination and for repair of DNA damaged by ultraviolet light, mitomycin C and ionizing radiation. The true extent of its involvement in these processes is masked to a large degree by what appears to be a functional overlap with the products of the three ruv genes. RuvA and RuvB act together to promote branch migration of Holliday junctions, while RuvC catalyses the resolution of these recombination intermediates into viable products by endonuclease cleavage. In this paper, we describe the overproduction and purification of RecG and demonstrate that the overlap extends to the biochemistry. We show that the 76 kDa RecG protein is a DNA-dependent ATPase, like RuvB. Using gel retardation assays we demonstrate that it binds specifically to a synthetic Holliday junction, like RuvA and RuvC. Finally, we show that in the presence of ATP and Mg2+, RecG dissociates these junctions to duplex products, like RuvAB. We suggest that RecG and RuvAB provide alternative activities than can promote branch migration of Holliday junctions in recombination and DNA repair. IMAGES: